The Erbaugh Scale: validity and reliability of an instrument to assess children's aquatic competence - Wizer, Rossane Trindade; Zanon, Cristian; de Souza Castro, Flávio Antônio; Guerra, Paulo Henrique [UNESP] (UNESP - Universidade Estadual Paulista, 2025)
Aim: The aim of this study was to perform a cross-cultural validation of the Erbaugh Scale, developed to assess children's aquatic competence. Methods: The authors translated the Erbaugh Scale to Brazilian Portuguese and tested it in Brazil with respect to internal consistency as well as content, criterion, and construct validity. The translation was performed by four professionals, and the content validation was performed by three researchers and five swimming teachers. Two teachers participated in the reliability analysis. Moreover, 368 children, from 36 to 72 months of age, participated in the study. Results: The original Erbaugh Scale was reduced from 68 to 47 items distributed in six aquatic tasks. The items were clear and relevant, with satisfactory values for the total content validity coefficient (clarity = 0.87; relevance = 0.91) and for the percentage of agreement between the judges (clarity = 87%; relevance = 75%). Factor analysis indicated a unifactorial solution, and the factor loadings of the tasks presented satisfactory values (0.558-0.956). The Scale correctly predicted and identified the aquatic competence of different age groups and previous aquatic experience. Considering internal consistency, Cronbach's alpha was 0.91. The intraclass correlation coefficients for intra- and inter-rater reproducibility were excellent (0.92-1.00), and there were no intra- and inter-rater differences (p > 0.05). Conclusion: The Erbaugh Scale proved to be valid and reliable for application in children in the context of teaching swimming.
Keywords: assessment; children; swimming; validation